Quality of Pharmaceutical Services and BPJS Patient Satisfaction at Dekai Hospital in 2025 - Syam, Ricky Aditya; Asmal, Adhitama (Borobudur Pharmacy Review, 2025)
Patient satisfaction with pharmaceutical services serves as a primary indicator in evaluating the quality of hospital care, particularly for BPJS patients undergoing outpatient treatment. This study aims to analyze the quality of pharmaceutical services and its relationship with patient satisfaction levels at RSUD Dekai in 2025. The method employed is a quantitative approach with a descriptive cross-sectional research design, involving 40 BPJS patient respondents seeking treatment at the hospital's pharmacy unit. Data were collected using a structured questionnaire and analyzed descriptively, while the relationships between variables were tested using the chi-square test on SPSS 26 at a significance level of 0.05. The findings indicate a significant influence of pharmaceutical service quality on patient satisfaction (p = 0.000 < 0.05). Notably, 92.5% of respondents reported satisfaction with the services, while 7.5% expressed dissatisfaction. These results suggest that pharmaceutical service quality is a key determinant in enhancing patient satisfaction. Accordingly, RSUD Dekai is recommended to implement ongoing improvements and enhancements to pharmaceutical operational procedures, thereby strengthening service reliability and elevating overall patient satisfaction.